2018
DOI: 10.3390/su10041156
|View full text |Cite
|
Sign up to set email alerts
|

International Migrant Remittances in the Context of Economic and Social Sustainable Development. A Comparative Study of Romania-Bulgaria

Abstract: The economic stability is the main goal of every country's administration, contributing to the decrease of uncertainty, creating an attractive business environment, attracting foreign direct investment and contributing to economic growth, which increases the standard of living, reduces income inequalities, represents a sustainable development for the country and puts an end to the migration process. Migration flows lower the demographic resources of the states going through this process and consequently they c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…For the individuals from G1, the odds ratio was not that high (oddsratio 2007 = 0.713 and oddsratio 2014 = 0.683), indicating that this perceptual variable had the lowest effect on the likelihood of involvement in TEA in both periods. Although, the odds ratio increased in 2014 for G2, it still remained the lowest among the individual-perception factors (see models (8), (9), (11) and (12) (Table 7). In 2014 the odds ratio for networking almost doubled, suggesting the strong effect of this variable on the propensity to engage in early-stage entrepreneurial activity (oddsratio 2007/G1 = 1.504 to oddsratio 2014/G1 = 2.869; oddsratio 2007/G2 = 1.898 to oddsratio 2014/G2 = 3.246).…”
Section: Results and Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…For the individuals from G1, the odds ratio was not that high (oddsratio 2007 = 0.713 and oddsratio 2014 = 0.683), indicating that this perceptual variable had the lowest effect on the likelihood of involvement in TEA in both periods. Although, the odds ratio increased in 2014 for G2, it still remained the lowest among the individual-perception factors (see models (8), (9), (11) and (12) (Table 7). In 2014 the odds ratio for networking almost doubled, suggesting the strong effect of this variable on the propensity to engage in early-stage entrepreneurial activity (oddsratio 2007/G1 = 1.504 to oddsratio 2014/G1 = 2.869; oddsratio 2007/G2 = 1.898 to oddsratio 2014/G2 = 3.246).…”
Section: Results and Interpretationmentioning
confidence: 99%
“…In 2014, for less developed economies, the follow up variables were gender (b * M = −0.052), age (b * M = −0.048), opportunity perception (b * M = 0.043), fear of failing (b * M = −0.043) and the interactions between gender and each perceptual factor. For high developed economies, the third importance in predicting early-stage entrepreneurial activity was fear of failing (b * M = −0.094), followed by age (b * M = −0.070), then opportunity perception (b * M = 0.044), gender (b * M = −0.039), and the interactions between gender and each perceptual factor (see (9) and (12), Table 9).…”
Section: Conclusion and Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this result is also supported by Mansoor and Quillin (2007) who showed the role of remittances in decreasing the poverty and in supporting saving. On long-run (1990On long-run ( -2015, Haller, Butnaru, and Butnaru (2018) showed that remittances did not ensure economic growth, but stimulated households final consumption and income inequality. Moreover, the remittances in Romania negatively affected exports' competitiveness and the motivation to work.…”
Section: Introductionmentioning
confidence: 99%
“…Also, rural students, more involved in household activities, spend less time on school activities. In this case, there may be mentioned situations in which students lose their lessons due to the impossibility of reaching school, which means a long recovery time [11].…”
Section: The High Share Of School Time In the Students' Daily Budgetmentioning
confidence: 99%